Does the hygiene hypothesis apply to COVID-19 susceptibility? - Sehrawat, Sharvan (Microbes Infect, 2020)
In this commentary we argue that the hygiene hypothesis may apply to COVID-19 susceptibility and also that residence in low hygienic conditions acts to train innate immune defenses to minimize the severity of infection. We advocate that approaches, which elevate innate immune functions, should be used to minimize the consequences of COVID-19 infection at least until effective vaccines and antiviral therapies are developed.